2008 Providence, Rhode Island, June 29 - July 2, 2008 2008
DOI: 10.13031/2013.25050
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spray application rate and droplet size on applications to control soybean rust

Abstract: Canopy penetration and thorough coverage are important when applying foliar fungicides to soybeans for the control of rust. The purpose of this study was to examine how spray application rate and spray droplet size affect the efficacy of soybean rust applications. Four treatments were examined: a medium droplet spectrum applied at 47 L/ha (5 GPA) and at 140 L/ha (15 GPA), and a very coarse droplet spectrum applied at 47 L/ha (5 GPA) and at 140 L/ha (15 GPA). Applications were made to soybeans planted with 91 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
6
0
2
Order By: Relevance
“…Such results agree with Bretthauer et al (2008), who verified a reduction of 12.1% in the MVD from the higher to the lower part when evaluating the spectrum of medium and thick droplets. Two other studies looked for answers on this subject: Yu et al (2009) confirmed influence of relative humidity on the droplet size reduction, which was 10 times faster when comparing droplets with 246μm and 800μm with 60% of relative humidity and reduction of MVD in the middle and lower part of the canopy.…”
Section: Medium Volumetric Diameter (Mvd) Relative Amplitude (Ra) Ansupporting
confidence: 91%
“…Such results agree with Bretthauer et al (2008), who verified a reduction of 12.1% in the MVD from the higher to the lower part when evaluating the spectrum of medium and thick droplets. Two other studies looked for answers on this subject: Yu et al (2009) confirmed influence of relative humidity on the droplet size reduction, which was 10 times faster when comparing droplets with 246μm and 800μm with 60% of relative humidity and reduction of MVD in the middle and lower part of the canopy.…”
Section: Medium Volumetric Diameter (Mvd) Relative Amplitude (Ra) Ansupporting
confidence: 91%
“…Nas três aplicações, foi verificada redução no DMV do terço superior para o inferior (Tabela 1). Bretthauer et al (2008), ao avaliar espectro de gotas médio e muito grosso para controle de ferrugem-asiática-da-soja, relataram que o DMV na porção inferior das plantas diminuía, em média, 12,6 e 11,6%, respectivamente.…”
Section: Resultsunclassified
“…Ozkan et al (2006) found medium droplet sizes resulted in greater coverage in the lower and middle portions of dense canopies of soybeans when compared to fine and coarse droplets. Bretthauer et al (2008) similarly observed greater control of soybean rust with very course droplet sizes. Hanna et al (2006), Prokop and Veverka (2006), and Derksen et al (2001) did not find droplet size to be a significant factor influencing efficacy of fungicides.…”
Section: Literature Reviewmentioning
confidence: 76%
“…Insecticide function relies on coverage of the plant for protection against pests. While coverage is higher in the upper canopy for smaller droplet sizes, penetration into the lower portions of the canopy is minimal (Bretthauer et al, 2008;Ozkan et al, 2006). A balance between small droplets for increased coverage and large droplets for increased penetration is achieved at the medium droplet size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation